SISTEM INFORMASI GEOGRAFIS PEMETAAN DAERAH RAWAN BANJIR DI KOTA SAMARINDA BERBASIS WEB - Syafei Karim; Winda Surmanti; Dawamul Arifin (Fakultas Teknologi Informasi Universitas Merdeka Pasuruan, 2022)
Floods are the most frequent natural disasters, both in terms of their intensity in one place and the number of locations in a year, which is around 40% of other natural disasters. Even in some places, flooding is an annual routine. The location of the incident can be urban or rural, developing countries or even developed countries. Geographic Information System (GIS) is one tool that can be used to assist the government in tackling flood-prone areas. In addition, GIS can also provide information to the public to be more vigilant. Therefore, the purpose of this research is to create a geographic information system for mapping flood-prone areas in the city of Samarinda based on a web that can assist the government in tackling flood-prone areas and provide information on flood-prone areas. to society.Keyword— GIS, prone areas, flooding, web, webGIS